Iron-based alloy powder for surface of hot rolling pinch roll, coating preparation method and coating
By using iron-based alloy powder on the surface of the hot-rolled pinch roller and using laser cladding technology, the coating problem in the prior art is solved, and the coating with high hardness and low friction coefficient is achieved, which significantly improves the surface quality and service life.
Patent Information
- Application Number
- CN202411952334.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing hot-rolled pinch roller surface coating, the process is complex, the hardness is not high enough, and pores, crack defects and steel sticking are prone to occur, which affects the surface quality and service life.
The iron-based alloy powder is used to improve the hardness and wear resistance of the alloy by adding elements such as Cr, V, N, Mo and S, and a high hardness and low friction coefficient coating is formed on the surface of the pinch roller through laser cladding technology.
It realizes the reduction of friction coefficient at high temperatures, solves the phenomenon of steel stickiness, and significantly reduces the wear rate, while improving the high-temperature wear resistance and thermal stability of the coating.
Smart Images

Figure CN119710489A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser cladding, and in particular relates to an iron-based alloy powder, a laser cladding coating and a preparation method thereof. Background Art
[0002] Laser cladding is a new type of surface modification technology. It uses a high-power density laser beam as a heat source to melt the powder pre-placed on the surface of the substrate or the powder fed in synchronously, and melts a certain surface of the substrate at the same time. The melted metal substrate surface forms a shallow molten pool. The molten pool and the molten powder material then cool and solidify to form a coating with good metallurgical bonding on the surface of the metal substrate. Laser cladding has the advantages of small heat input, fine grain structure of the prepared coating, small heat-affected zone and dilution rate, and has great development potential. With the development of laser technology, laser cladding technology has been widely used in the modification of the surface of mechanical parts.
[0003] The pinch roller of the hot strip coiler is one of the key components of the steel rolling equipment. Its main function is to pull the rolled high-temperature steel plate into the coiler for coiling and winding. Therefore, it is under high temperature and high pressure working conditions. There is an urgent need for the high-temperature wear resistance of the pinch roller surface, and it is usually necessary to melt-coat a wear-resistant coating on its surface. Most of the commonly used coating preparation technologies currently have complex processes, insufficient coating hardness, easy to have pores, cracks, and easy to stick to steel, which affects the surface quality and service life of the pinch roller. In response to the above problems, the coating needs to have a certain lubrication performance while having a high hardness to reduce the friction coefficient during the wear process and reduce the phenomenon of sticking to steel. Summary of the invention
[0004] The problem to be solved by the present invention is to provide an iron-based alloy powder for the surface of a hot rolling pinch roller, which reduces the cutting effect of abrasive particles by adding a lubricating phase, reduces the friction coefficient at high temperature, solves the problem of steel sticking, and reduces the wear rate; at the same time, it has good high-temperature wear resistance and thermal stability. In addition, the present invention also provides a laser cladding coating on the surface of a hot rolling pinch roller and a preparation method thereof.
[0005] The iron-based alloy powder for the surface of the hot-rolled pinch roller of the present invention is composed of the following elements in percentage by mass: C: 0.16-0.2%, Si: 0.78-1.0%, Cr: 14.3-17%, Ni: 7.8-8.2%, Mn: 0.09-0.12%, the total amount of Mo and S: 1.9-4.0%, the total amount of V and N: ≤7.2%, and the rest is Fe.
[0006] Furthermore, the mass percentages of the elements in the iron-based alloy powder are as follows: C is 0.18%, Si is 0.92%, Cr is 16.8%, Ni is 7.83%, Mn is 0.11%, Mo is 1.95%, the total amount of V and N is 7.0%, and the rest is Fe.
[0007] Furthermore, the mass percentages of the elements in the iron-based alloy powder are as follows: C is 0.18%, Si is 0.92%, Cr is 16.8%, Ni is 7.83%, Mn is 0.11%, the total amount of Mo and S is 3.95%, and the rest is Fe.
[0008] Furthermore, the mass percentages of the elements in the iron-based alloy powder are: C is 0.18%, Si is 0.92%, Cr is 16.8%, Ni is 7.83%, Mn is 0.11%, the total amount of Mo and S is 3.95%, the total amount of V and N is 7.0%, and the rest is Fe.
[0009] Furthermore, the particle size of the iron-based alloy powder is 53-150 μm.
[0010] The iron-based alloy powder of the invention is prepared by a ball milling method.
[0011] The method for preparing the laser cladding coating on the surface of a hot rolling pinch roller of the present invention uses argon as a protective gas, laser as a heat source, powder is fed in a conical powder beam manner, the scanning speed, laser power and powder feeding rate are controlled, the heat generated by the laser beam is used to melt the surface of the substrate and the iron-based alloy powder, a single cladding layer is formed on the surface of the substrate, and the aforementioned steps are repeated to obtain multiple cladding layers.
[0012] Furthermore, during laser cladding: the scanning speed is 3-5 mm / s, the laser power is 1.2-1.8 kW, and the powder feeding rate is 12-18 g / min.
[0013] Furthermore, the thickness of a single cladding layer is 1-1.5 mm, and the base material dilution rate is 2-5%.
[0014] The coating obtained by laser cladding of the present invention has an HRC of ≥55.
[0015] The advantages of the iron-based alloy powder of the present invention are: 1. The Cr element content is relatively high: (1) The Cr atomic radius is different from that of iron, which will cause lattice distortion in the iron lattice, thereby hindering the movement of dislocations and improving the strength and hardness of the material; (2) Chromium and carbon form carbides (such as Cr 23C6), these carbides are distributed in the iron-based alloy in the form of fine particles, playing a role of dispersion strengthening; at the same time, the carbides formed by chromium precipitate at the grain boundaries, hindering the growth of grains and producing a fine grain strengthening effect; 2. Adding appropriate amounts of V and N elements: (1) As a high-temperature resistant element, V will increase the lattice constant of iron, causing lattice distortion, thereby increasing the resistance to dislocation movement and improving the strength and hardness of the alloy; this solid solution strengthening effect is particularly obvious at high temperatures and helps to improve wear resistance; (2) Carbides formed by vanadium and carbon (such as VC) can precipitate at the grain boundaries. (3) Vanadium carbides have good thermal stability at high temperatures and are not easy to aggregate and grow, thus maintaining the high temperature performance of the alloy and improving the thermal stability of the iron-based alloy. (4) As an interstitial element, nitrogen can replace the position of iron atoms in the lattice of the iron-based alloy to form a solid solution. Since the radius of nitrogen atoms is different from that of iron atoms, this substitution will cause lattice distortion and increase the resistance to dislocation movement. (5) When nitrogen and alloying elements such as Cr work together, they form The carbonitride or nitride precipitation phases are formed. These hard phases are precipitated in the crystal or at the grain boundary, which increases the obstacle of dislocation movement and improves the strength of the material. Third, a certain amount of S and Mo elements are added: (1) Molybdenum sulfide has a layered structure, and interlayer slip occurs under the action of shear force, thereby forming a lubricating film on the coating surface, which greatly reduces the friction coefficient. In addition, during the friction process, molybdenum sulfide can transfer to the metal surface to form a uniform and continuous transfer film, which can further reduce the friction coefficient. Therefore, although the hardness of molybdenum sulfide itself is not high, it can (1) Reduce direct metal-metal contact, thereby reducing the wear rate, and the reduction in friction coefficient reduces the phenomenon of steel sticking; (2) The addition of molybdenum sulfide can promote the formation of other hard phases in the coating, such as carbides or borides, which can improve the overall hardness and wear resistance of the coating; (3) Due to the low decomposition temperature of molybdenum sulfide, in an inert atmosphere, molybdenum sulfide will sublime at 450°C, begin to decompose at 1370°C, and completely decompose into metallic molybdenum and sulfur at 1600°C; molybdenum sulfide is coated with nickel to reduce its decomposition during the laser cladding process. In short, the addition of the lubricating phase in the material of the present invention reduces the cutting action of the abrasive particles, reduces its friction coefficient at high temperature, solves the problem of steel sticking, and reduces the wear rate; at the same time, the material of the present invention has good high-temperature wear resistance and thermal stability.
[0016] The advantages of the preparation method of the laser cladding coating of the present invention are as follows: First, a good coating forming effect is achieved by controlling the parameters of scanning speed, laser power and powder feeding rate: if the scanning speed is too low or the laser power is too high, the coating dilution rate is high, and the coating components will be contaminated by the substrate components; if the scanning speed is too high or the laser power is too low, the coating layer thickness is thin, the process efficiency is low, and even the coating and the substrate are not metallurgically bonded; if the powder feeding rate is too low, the relative heat input will be too large, the coating dilution rate will be high, and the coating components will be contaminated by the substrate components; if the powder feeding rate is too high, a large amount of powder will be wasted, and to a certain extent, the same situation as that caused by excessive scanning speed or too low laser power will occur; Second, the smaller substrate dilution rate (2-5%) and the thicker single-pass cladding coating thickness (1-1.5mm) make the laser cladding have a higher efficiency, the iron-based alloy powder component of the coating is well guaranteed, and the coating and the substrate are also achieved A close metallurgical bond is achieved; at the same time, the prepared coating has high performance without defects such as cracks and pores on the surface and inside: the thicker the thickness of the single-pass cladding layer, the higher the efficiency of the process, which is beneficial to actual production operations, but the increase in the thickness of the single-pass cladding layer will increase the tendency of pores and cracks in the cladding layer, thereby reducing the performance of the coating. Therefore, under the condition that no defects are generated in the cladding layer, the thicker the single-pass cladding layer, the better; if the dilution rate is too high, the chemical elements in the substrate will enter the cladding layer, causing the chemical composition of the cladding layer and the powder composition to deviate, thereby affecting the performance and use of the cladding layer. Therefore, under the condition that the cladding layer and the substrate form a metallurgical bond, the lower the dilution rate, the better; 3. The particle size of the iron-based alloy powder is 53-150μm to ensure the fluidity of the powder and obtain good feeding quality: if the powder particle size is too small, its fluidity is very poor and it cannot be fed using the coaxial powder feeding method; if the powder particle size is too large, it is easy to splash and lose during the feeding process. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a cross-sectional macroscopic morphology of the laser cladding coating in Example 3;
[0018] Figure 2 is a microstructure morphology of the laser cladding coating in Example 3;
[0019] Figure 3 It is the microstructure diagram of four coatings S1-S4 in the comparative test example;
[0020] Figure 4 is the EDS surface scanning result diagram of the laser cladding coating in Example 3;
[0021] Figure 5 This is an EDS surface scanning result diagram of the worn surface of the laser cladding coating in Example 3 after high temperature wear;
[0022] Figure 6 It is a graph of the wear performance of four coatings S1-S4 in the comparative test example. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0024] Example 1
[0025] 1. Preparation of iron-based alloy powder
[0026] The iron-based alloy powder is prepared by ball milling. The composition of the iron-based alloy powder is: 0.18% C, 0.92% Si, 16.8% Cr, 7.83% Ni, 0.11% Mn, 1.95% Mo, the total amount of V and N is 7.0%, and the rest is Fe. The particle size of the iron-based alloy powder is 53-150μm.
[0027] 2. Preparation of laser cladding coating
[0028] 42CrMo steel was selected as the substrate with a size of 200mm×80mm×20mm. The surface of the substrate was polished with a grinder before cladding and then cleaned with acetone. An 8kW high-power semiconductor laser cladding system was selected, with argon as the protective gas, laser as the heat source, and powder feeding in a conical powder beam manner. The scanning speed was 5mm / s, the laser power was 1.8kW, and the powder feeding rate was about 18g / min. A laser cladding coating with a single cladding layer was obtained, the coating thickness was 1.0mm, and the substrate dilution rate was 4.8%; the hardness of the coating was HRC61.8.
[0029] Example 2
[0030] 1. Preparation of iron-based alloy powder
[0031] The specific method is the same as step 1 in Example 1, except that the composition of the iron-based alloy powder is: C is 0.18%, Si is 0.92%, Cr is 16.8%, Ni is 7.83%, Mn is 0.11%, the total amount of Mo and S is 3.95%, and the rest is Fe. The particle size of the iron-based alloy powder is 53-150μm.
[0032] 2. Preparation of laser cladding coating
[0033] The specific method is the same as step 2 in Example 1, except that during laser cladding, the scanning speed is controlled at 3 mm / s, the laser power is 1.2 kW, the powder feeding rate is about 15 g / min, and a laser cladding coating of a single cladding layer is obtained. The coating thickness is 1.2 mm, and the substrate dilution rate is 2.1%; the hardness of the coating is HRC56.
[0034] Example 3
[0035] 1. Preparation of iron-based alloy powder
[0036] The specific method is the same as step 1 in Example 1, except that the composition of the iron-based alloy powder is: C is 0.18%, Si is 0.92%, Cr is 16.8%, Ni is 7.83%, Mn is 0.11%, the total amount of Mo and S is 3.95%, the total amount of V and N is 7.0%, and the rest is Fe, and the particle size of the iron-based alloy powder is 53-150μm.
[0037] 2. Preparation of laser cladding coating
[0038] The specific method is the same as step 2 in Example 1, except that during laser cladding, the scanning speed is controlled at 4 mm / s, the laser power is 1.5 kW, and the powder feeding rate is about 12 g / min to obtain a laser cladding coating with a single cladding layer.
[0039] like Figure 1 As shown, the thickness of the laser cladding coating obtained in this embodiment is about 1.4 mm, there are no defects such as cracks, pores, inclusions, etc. in the coating, and the coating is well bonded to the substrate. In addition, the substrate dilution rate is measured to be 3.7%, and the hardness of the coating is HRC61.
[0040] like Figure 2 As shown, the microstructure of the laser cladding coating obtained in this embodiment is a martensite+eutectic carbide+retained austenite organization, which can have good wear resistance and crack resistance at a high temperature of 300°C.
[0041] from Figure 5 It can be seen that the Mo, S, V, and N elements in the laser cladding coating obtained in this embodiment are evenly distributed, and the Cr oxide on the surface is the main reason for the wear of the coating at high temperature.
[0042] Two cladding powders and one commercial powder are taken as comparative alloy powders of the present invention. The cladding layers made of the two cladding powders are marked as S1 and S2. The laser cladding coating prepared by the commercial powder using the method of step 2 of Example 1 is marked as S3. The laser cladding coating prepared by Example 3 of the present invention is marked as S4. The comparative test examples are as follows:
[0043] 1. Comparison of coating microstructure: Figure 3 The metallographic structures of the four coatings S1, S2, S3, and S4 are shown in Figure 2. It can be seen that the coatings of the four iron-based alloy powders all have a microstructure of martensite + carbide second phase, and the cladding layer structures all show typical dendrite characteristics, but there are certain differences in the carbide content and coating grain size. In comparison, the grains of the S3 and S4 laser cladding coatings are finer than those of the S1 and S2 cladding coatings, and the carbide content is also higher. Figure 4 It can be seen that: V element as a strengthening element is in the form of a particle phase in the coating. The precipitation of V3N particles can hinder the movement of dislocations and help to refine the grains of the iron-based alloy, thereby enhancing the strength of the material.
[0044] 2. Comparison of wear resistance: Tungsten carbide was used as the friction pair to conduct high temperature friction and wear tests on the three comparative examples and embodiments 1-3 of the present invention, with a test load of 50N, a rotation speed of 200rpm, a temperature of 300℃, and a test time of 60min. Table 1 shows the friction coefficient and wear data of each cladding coating and laser cladding coating. Figure 5 It can be seen that the strengthening phase and lubricating phase formed by V and Mo elements are evenly distributed in the coating, ensuring the wear resistance of the coating.
[0045] Table 1
[0046]
[0047] From Table 1 and Figure 6 It can be seen that: (1) Compared with the cladding coatings S1 and S2, the high-temperature wear resistance of the laser cladding coating is greatly improved. The main reason is that the rapid cooling and heating characteristics of laser cladding make the coating grains finer, the total number of grain boundaries is greater, and the dislocation movement is more hindered, thereby improving the yield strength of the material; and during the wear process, the fine grains can distribute stress more evenly, reduce local stress concentration, and thus reduce the wear rate; (2) The wear resistance of the S3 coating is slightly higher than that of the S1 and S2 coatings. The S3 coating has a lower wear amount, but the friction coefficients of S1, S2, and S3 are similar; the present invention reduces the cutting effect of the abrasive particles by adding a lubricating phase to the material, thereby reducing the friction coefficient at high temperature, solving the problem of steel sticking, and reducing the wear rate. Therefore, the performance of Examples 1, 2, and 3 (S4) is better than that of S1, S2, and S3. Considering the comprehensive friction coefficient and hardness, the wear resistance of the coating of Example 3 (S4) is relatively the best.
[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Iron-based alloy powder for hot rolling pinch roll surface, characterized by: It is composed of the following elements in percentage by mass: C: 0.16-0.2%, Si: 0.78-1.0%, Cr: 14.3-17%, Ni: 7.8-8.2%, Mn: 0.09-0.12%, the total amount of Mo and S: 1.9-4.0%, the total amount of V and N: ≤7.2%, and the rest is Fe.
2. The iron-based alloy powder according to claim 1, characterized in that: The mass percentages of the elements are: C: 0.18%, Si: 0.92%, Cr: 16.8%, Ni: 7.83%, Mn: 0.11%, Mo: 1.95%, the total amount of V and N: 7.0%, and the rest is Fe.
3. The iron-based alloy powder according to claim 1, characterized in that: The mass percentage of the elements is: C: 0.18%, Si: 0.92%, Cr: 16.8%, Ni: 7.83%, Mn: 0.11%, the total amount of Mo and S: 3.95%, and the rest is Fe.
4. The iron-based alloy powder according to claim 1, characterized in that: The mass percentages of the elements are: C: 0.18%, Si: 0.92%, Cr: 16.8%, Ni: 7.83%, Mn: 0.11%, the total amount of Mo and S: 3.95%, the total amount of V and N is 7.0%, and the rest is Fe.
5. The iron-based alloy powder according to claim 1, characterized in that: The particle size is 53-150μm.
6. The iron-based alloy powder according to claims 1-5, characterized in that: Prepared by ball milling method.
7. A method for preparing a laser cladding coating on the surface of a hot rolling pinch roll, characterized in that: Argon is used as a protective gas, laser is used as a heat source, powder is fed in a conical powder beam manner, scanning speed, laser power and powder feeding rate are controlled, the heat generated by the laser beam is used to melt the surface of the substrate and the iron-based alloy powder according to claims 1 to 5, a single cladding layer is formed on the surface of the substrate, and the aforementioned steps are repeated to obtain multiple cladding layers.
8. The preparation method according to claim 7, characterized in that: The scanning speed is 3-5 mm / s, the laser power is 1.2-1.8 kW, and the powder feeding rate is 12-18 g / min.
9. The preparation method according to claim 7, characterized in that: The thickness of a single cladding layer is 1-1.5 mm, and the substrate dilution rate is 2-5%.
10. The coating obtained according to claims 7-9, having an HRC ≥ 55.